A computational fluid dynamics (CFD) model for effective coolant application in deep hole gundrilling. (February 2017) - Woon, K.S.; Tnay, G.L.; Rahman, M.; Wan, S.; Yeo, S.H.
Abstract: Effective coolant application in deep hole gundrilling is crucial to prevent rapid degradation and failure of drills through high performance cooling, lubrication and chip evacuation. This paper presents a novel methodology to increase effectiveness of coolant application through strategic optimization of gun drill designs that leads to appreciable tool life improvement, based on computational fluid dynamics (CFD) analysis. Through the analyses of coolant flow characteristics and rheological properties, conventional designs of critical drill geometries like nose grind contour, coolant hole configuration and shoulder dub-off angle, which are detrimental to coolant application and hence tool life are determined. A new, optimized gun drill design for the drilling of deep holes on Ni-based alloys is proposed. All findings are experimentally substantiated.